Neutrophil extracellular traps as drivers of epithelial-mesenchymal transition in cancer cells - Maddalena, Maurizio; Dimitrov, Jelena; Mehmood, Tayyaba; Terlizzi, Cristina; Esposito, Paola Maria Helena; Franzese, Antonella; Pellegrino, Sara; De Rosa, Viviana; Iommelli, Francesca; Del Vecchio, Silvana (Frontiers in Immunology, 2025)
Neutrophil extracellular traps (NETs) are complex structures released by activated neutrophils and composed by double-stranded DNA associated with histones and an arsenal of proteases and proteins. NETs are reported to be present in tumors and blood of cancer patients where they can directly or indirectly modulate different functions of cancer cells. Here, we will summarize the current evidences indicating that NETs can drive tumor growth and metastatic dissemination through different signaling pathways. Many studies reported that NETs can enhance cancer cell proliferation and promote colonization of distant sites by circulating cancer cells, especially in the presence of sepsis and surgical stress. However, there are scattered reports on the ability of NETs to induce epithelial-mesenchymal transition (EMT) in different contexts. In this minireview, we will focus especially on the studies investigating the induction of EMT by NETs trying to highlight the involvement of specific signaling pathways. The results of these studies delineate an intricate scenario in which NETs stay at the crossroad between inflammation and cancer playing a leading role in metastatic dissemination by inducing EMT through different signaling pathways.